Pengaruh Kompensasi Finansial Dan Non Finansial Terhadap Loyalitas Karyawan Dan Dampaknya Terhadap Kinerja Karyawan Pada PT. Serambi Nusantara - Siti Aesah; Agustina Mogi; Krida Puji Rahayu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of financial and non-financial compensation on employee loyalty and its impact on employee performance at PT. Serambi Nusantara. Using a quantitative approach and multiple linear regression analysis with SPSS on 30 respondents, the study found that both financial and non-financial compensation have a significant effect on employee loyalty, both partially and simultaneously. Furthermore, employee loyalty was found to have a positive impact on employee performance. These findings emphasize the importance for companies to balance financial compensation with non-financial aspects—such as recognition, career development, and a supportive work environment—in order to enhance employee loyalty and improve overall performance sustainably.